"Ancient" schwannoma of the submandibular gland: A case report and literature review. Issue 51 (December 2017) - Ho, Che-Fang; Wu, Pei-Wen; Lee, Ta-Jen; Huang, Chien-Chia
Abstract: Rationale: Schwannomas are solitary neurogenic tumors that arise from cells of the neural sheath. Ancient schwannoma is a relatively rare variant of schwannoma, characterized by increased cellularity and atypia. These cellular changes could be confusing and make the accurate pathologic diagnosis difficult. Patient concerns and diagnoses: A 36-year-old man presented with painless swelling in left submandibular region for more than 2 years. The computed tomography confirmed a well-defined cystic lesion in the left submandibular space, which caused superior and posterior displacement of the left submandibular gland. Surgical excision was performed and the pathology confirmed the diagnosis of ancient schwannoma. To our knowledge, this patient is the second case of primary submandibular ancient schwannoma reported in the literatures. Interventions and outcomes: The patient underwent tumor resection and postoperative recovery was uneventful. There were no nerve deficits after the operation. There was no recurrence within 1 year of follow-up. Lessons: Schwannoma originated from the submandibular gland is extremely rare and only a few cases have been reported. Ancient schwannoma is an even more rare tumor. The increased cellularity and atypia of ancient schwannoma can resemble features of malignancy. Great care must be taken to make differential diagnosis with fibrosarcomas and malignant schwannoma.